Lécba Hodgkinovy choroby podle protokolu Nĕmecké studijní skupiny. Nase zkusenosti a výsledky - Marková, J; Kocová, J; Malinová, B; Stríteský, J; Feltl, D; Diehl, V (Vnitrni lekarstvi, 2000)
UNLABELLED: The article present an evaluation (02/1999) of the study of primary treatment of Hodgkin's disease (HD) according to the third generation of the German Hodgkin's Disease Study Group (GHSG), and our experience with this treatment strategy. HD7 study of early stages HD showed better results (fewer relapses) for combined chemo and radiotherapy than for radiotherapy alone (2x ABVD + extended field radiotherapy compared to extended field radiotherapy alone). HD8 study of intermediate stage HD did not show any difference between chemotherapy 2x (COPP + ABVD) combined with radiotherapy extended field, or involved field. Due to the long-term consequences (especially secondary neoplasm), in the current (fourth) generation protocol extended field radiotherapy in early and intermediate stage HD has been replaced by a combination of lesser toxic chemotherapy and involved field radiotherapy. HD9 study of advanced HD. The standard treatment at present of COPP/ABVD (A) was compared with the new chemotherapeutic regimen, BEACOPP baseline (B) and escalated (C). The first evaluation of this study (1996) showed better results in the case of BEACOPP. The latest evaluation showed significantly better results for the escalated version. This is best illustrated by the low percentage of disease progression (C 2%, B 8%, A 12%, p < 0.05). Therefore, DHSG is considered to be the new standard for treatment of advanced stage HD. OUR RESULTS: Between 1995-1998, 54 patients with primary HD were treated at the FN Královaké Vinohrady, Prague according to the third generation GHSG protocol. Of these, 5 patients (9%) according to HD7, 14 (26%) according to HD8 and 35 patients (65%) according to HD9. Our results correspond to those of the whole GHSG, but they can not be statistically evaluated because of the small number of patients involved.
Keywords: senioři; Antineoplastic Combined Chemotherapy Protocols; Middle Aged; Hodgkinova nemoc; Combined Modality Therapy; protokoly protinádorové kombinované chemoterapie; dospělí; Humans; Adult; Recurrence; Hodgkin Disease; Aged; recidiva; kombinovaná terapie; lidé; lidé středního věku